Meatless? : a fresh look at what you eat - Elton, Sarah, 1975- (Owlkids Books, 2017)
Examines the reasons why people choose to eat the way they do, looking at such reasons as health, taste, ethics, religion, and environmental concerns, and discusses a vegetarian lifestyle.